2022
DOI: 10.1038/s41562-022-01410-x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic regularities in infant-directed speech and song across cultures

Abstract: Humans often produce vocalizations for infants that differ from vocalizations for adults. Is this property common across societies? The forms of infant-directed vocalizations may be shaped by their function in parent-infant communication. If so, infant-directed song and speech should be differentiable from adult-directed song and speech on the basis of their acoustic features, and this property should be relatively invariant across cultures. To test this hypothesis, we built a corpus of 1,614 recordings of inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(130 citation statements)
references
References 117 publications
10
120
0
Order By: Relevance
“…This research builds on previous studies from our group (Hilton, Moser, et al, 2022;Mehr et al, 2019, demonstrating (a) cross-cultural regularities in the associations between acoustical forms of music and particular behavioral contexts in which music appears; and (b) the sensitivity of adults to these associations. Here, we explored how musical experience in childhood shapes that sensitivity, using the same stimuli as previous work.…”
Section: Context Of the Researchmentioning
confidence: 70%
“…This research builds on previous studies from our group (Hilton, Moser, et al, 2022;Mehr et al, 2019, demonstrating (a) cross-cultural regularities in the associations between acoustical forms of music and particular behavioral contexts in which music appears; and (b) the sensitivity of adults to these associations. Here, we explored how musical experience in childhood shapes that sensitivity, using the same stimuli as previous work.…”
Section: Context Of the Researchmentioning
confidence: 70%
“…We selected these features by reviewing what past studies focused on for the analysis of song-speech comparison and prominently observed features in music (e.g. Fitch, 2006;Hansen et al, 2020;Hilton et al, 2022;Savage et al, 2015;Sharma et al, 2021, see the Supplementary Discussion section S1.1 for a more comprehensive literature review). Here, f 0 , rate of change of f 0 , and spectral centroid are extracted purely from acoustic signals, while IOI rate is based purely on manual annotations.…”
Section: Featuresmentioning
confidence: 99%
“…In music, these include regular rhythms, discrete pitches, small melodic intervals, and a predominance of songs with words (rather than instrumental music or wordless songs) (Mehr et al, 2019;Savage et al, 2015). However, non-signed languages also use the voice to produce words, and other proposed musical universals may also be shared with language (e.g., discrete pitch in tone languages; regular rhythms in "syllable-timed" / "stress-timed" languages; use of higher pitch when vocalizing to infants) (Haiduk & Fitch, 2022;Hilton et al, 2022;Patel, 2008;Tierney et al, 2011). Moreover, vocal parameters of speech and singing, such as fundamental frequency and vocal tract length as estimated from formant frequencies, are strongly intercorrelated in both men and women (Valentova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations